Study To Assess Awareness About HIV / AIDS Among First Year MBBS Students in A Medical College, Vijayapura, Karnataka - Patil, Santosh D; Bhovi, Ravindranath A (National Journal of Community Medicine, 2016)
Introduction: The lack of awareness and misconceptions about HIV/AIDS in general population is responsible for rapid spread and social stigma & discrimination in our country. Many studies have revealed that early educational interventions can reduce the Knowledge Attitude Practice (KAP) gap among health professionals. This study was conducted to assess awareness regarding HIV/AIDS in newly admitted medical students. Methodology: A cross sectional study was conducted on MBBS students of BLDEU Shri B. M. Patil medical college Vijaypur from December 2015 to January 2016.A total of 135 students were interviewed using pretested questionnaire. Descriptive statistics was used to analyze the data. Results-Awareness among students about HIV was good. All the students (100%) were conscious about HIV/AIDS disease, its causative agent and diagnostics test. Majority of the students were aware about the modes of transmission and preventive approaches. Very few misconceptions were observed like spread by mosquito bite. Conclusion –The results of our study are encouraging as most of students had good awareness regarding HIV/AIDS disease. Role of media & IEC activities are very important to spread the awareness among general population. These measures will help to reduce the misconception and indifferent attitude towards the HIV infected patients.